Dampak Perkembangan Teknologi Informasi dan Komunikasi terhadap Perilaku Intoleransi dan Antisosial di Indonesia - Rafles Abdi Kusuma (Mawaizh : Jurnal Dakwah dan Pengembangan Sosial Kemanusiaan, 2019)
The paper aims to exploration how the impact of the information and technology development in Indonesia. Especially, focus on the raising of the attitude and behavior that tend toward intolerant and antisocial. That behavior and attitude extremely were disturbing our social life. The flood of information in cyberspace causes disinformation that makes people split into poles of homogeneity, so people are not accustomed to a difference and are not trained to see problems from various sides. The transformation process taking place with a multilayer communication model has resulted in humans who are more individualistic and communalism, which leads to intolerant and antisocial behavior. Even today, communities are still divided into groups called "cebong" and "kampret". These two political poles cause people did not respect each other's differences. They spread hatred of speech and reject each other's activities, including worship activities. If this kind of social condition is allowed to leave, Indonesia will always be in an unsafe and comfortable condition. It should be prevented by knowing various characteristics or symptoms that arise from the behavior of people around us, both directly in the real world and through social media. Therefore, the authors offer a solution namely: strengthening the role of religion, especially in da'wa and internalization of the ideology of Pancasila, the enforcement of the constitution and humanist legal rules in Indonesia.